The Alma Survey of Gas Evolution of Protoplanetary Disks (Age-Pro). Xii. Extreme Millimeter Variability Detected in a Class Ii Disk - Miley, J; Gonzalez-Ruilova, C (Institute of Physics, 2025)
Variability of millimeter wavelength continuum emission from Class II protoplanetary disks is extremely rare, and when detected, it is usually interpreted as originating from nonthermal emission mechanisms that relate to the host star itself rather than its disk. During observations made as part of the AGE-PRO Large Program, significant variability in the brightness of the 2MASS J16202863-2442087 system was detected between individual executions. We report the observed properties of the variability detected at millimeter wavelengths and investigate potential driving mechanisms. To investigate the nature of the variability, we construct a light curve from the continuum observations and analyze images constructed from both flaring and quiescent emission. We characterize the dust disk around the star through analysis in the image and visibility plane, and carry out kinematic analysis of CO (2-1) emission from the gas disk. The continuum flux decays by a factor of 8 in less than an hour, and by a factor of 13 within 8 days. The peak brightness coincides with an expected brightness maximum extrapolated from the periodicity of previously observed optical variability. The flare is most likely the product of synchrotron emission in the close vicinity of the star. The nature of the millimeter flare closely resembles those detected in very close binary systems, and may be due to the interaction of magnetic fields in an as-yet undetected binary. Alternatively, if the central host is a single-star object, the flare may be due to the interaction of magnetic field loops at the stellar surface or a strong accretion burst. © 2025. The Author(s). Published by the American Astronomical Society.